Grammatical Aspect as a Means of Optimizing the Educational Process - Baxadirova, Muxiba Abdukarimovna (European Journal of Life Safety and Stability (2660-9630), 2022)
this article provides the formation of students’ ability to use grammar as a multifunctional means of communication. Therefore, author gives several advices to teachers how to achieve grammatical correctness of students’ speech. In addition, in this article there are some researches where the grammatical aspect is optimizing the learning process.